Ürojinekolojide ve Kadın İnkontinansında Güncel Perspektif - Gürel, Duygu; Kol, Arif; Körkoca, Ayfer; İpek, Osman Murat; Malak, Arzu; Keten, Tanju; Doğrusever, Mehmet Burak; Dayısoylu, Hulusi Sıtkı; Şahin, Mehmet Fatih; Özcan, Rıdvan; Tok, Doğan Sabri; Akyol, Safa; et al. (2023)
-